South Tyrol's negotiated autonomy - Alber, Elisabeth (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The study of South Tyrol's negotiated autonomy is both a way of understanding how the Italian Alpine area successfully accommodated its linguistic groups (German-, Italianand Ladin-speakers), and why there are diverging opinions on how to revise its Second Autonomy Statute of 1972. The paper examines key actors and procedural mechanisms that contributed to the creation and implementation of South Tyrol's power-sharing system and minority regime. Firstly, it highlights the conflict settlement at international level in the aftermath of Second World War. Secondly, it scrutinizes the functioning of special bodies (the Commission of 19 and the Commission of Six) that crucially contributed to setting up South Tyrol's self-government regime. Thirdly, it gives evidence on both the legal framework as well as the bodies of the Autonomy Convention, a largescaled consultative process that has the task to come up with proposals on how to revise the Second Autonomy Statute.
Keywords: Italija; Italy; Južna Tirolska; narodne manjšine; autonomy; avtonomija; pogajanja; Konvencija o avtonomiji